Penerapan Supervisi Akademik Dalam Meningkatkan Pendidikan di SDS Mitra Sejati - Wasiyem, Wasiyem; Maysarah, Nursiti; Muthmainnah, Fadhillah; Simanjuntak, Sri Nurjamilah; Rambe, Awaluddin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The standard of education in a nation has an effect on its progress. Through interaction between students, educators, and learning resources, education is a teaching and learning activity. The rest is influenced by the community and the environment around it, but these three main factors greatly influence the quality of education. It is hoped that every member of the educational staff and teaching staff will comprehend the significance of educational supervision in the learning process in order to support the improvement of education quality. so that each educator and education staff member can fulfill their supervisory duties in accordance with their rights and authority. It is anticipated that education will produce the nation's next generation with academic and non-academic potential to compete nationally and internationally. In Indonesia, education supervision serves to restore and improve the educational system. However, in practice, educational supervision still suffers from a number of flaws, including supervisors who have not been able to perform their responsibilities to the fullest, a lack of awareness of the significance of educational supervision to the creation of high-quality education, and a lack of infrastructure for educational supervision.. Keywords: Academic Supervision, Quality of Education.